Development of an artificial mass-rearing method for Anastrepha fraterculus (Wied.) (Diptera: Tephritidae) - Flores, Hector S.; Hernández, Emilio; Toledo, Jorge (Instituto de Ecología, A.C., 2012)
A methodological process is described here to solve two bottle necks that render the establishment of fruit flies under artificial conditions for mass production difficult. The first was the selection of an oviposition system and the second the adaptation to the artificial diet used for larval development. Females preferred to oviposit on yellow spheres, and on white organza cloth flat panels covered with transparent silicon. A larval diet used to rear A.ludens, allowed the highest larval development, survival from egg to larva was 26.9%, larval weight 19.6mg, pupation at 24 h 97.7%, pupal weight 16.7mg and adult emergence 83.3%. Survival curves (nx, 1x) and life expectancy (ex) indicated at least 50% of the adults survive ~40 days. Life expectancy was of 34.74 days. The reproductive rate was 345.38 daughters/mother/generation; the intrinsic rate of population growth was 0.35days-1; while the median generation time and the time of duplication were 16.82 and 20.2 days, respectively. Moreover, we discuss results based on quality control parameters of insects after of 16 generations in mass-rearing under artificial conditions.